Recurrent kala-azar: report of two cured cases after total splenectomy - Reinaldo, Luis Gustavo Cavalcante; Araújo Júnior, Raimundo José Cunha; Diniz, Thiago Melo; Moura, Rafael de Deus; Costa, Dorcas Lamounier; Eulálio, Kelsen Dantas; Costa, Carlos Henrique Nery (Revista do Instituto de Medicina Tropical de São Paulo, 2020)
In Latin America, the causative agent of kala-azar is the intracellular protozoan Leishmania infantum. Most cases in South America are reported in Brazil. Worldwide, it mainly affects Bangladesh, Ethiopia, India, South Sudan and Sudan. Despite the high morbidity and lethality of kala-azar, most infections are asymptomatic. However, a small portion of patients evolves with recurrence of kala-azar becoming symptomatic even after all available drug treatments. Kala-azar is not a formal indication for splenectomy in adults. Splenectomy is recommended as a saving measure, when kala-azar is associated with symptomatic hypersplenism and for drug-resistant cases. In the study, we report two cases of kala-azar with splenomegaly that presented several hospitalizations due to the recurrence of the kala-azar, in addition to hospitalizations for normalizing the blood count. After splenectomy, kala-azar cases and the effects of hypersplenism are cured. Thus, splenectomy should be seen as a surgical treatment option with a curative purpose in patients with recurrent kala-azar, in whom the possibilities of drug therapy have been exhausted and even so they progressed with hypersplenism and clinical repercussions.